Biaya PolitikTinggi - Sebab Akibat Tingginya Biaya Pemilu Di Indonesia - Sujatmiati; Wiranto, Erham Budi (Bestuurskunde: Journal of Governmental Studies, 2024)
This research stems from the issue of lack of transparency in the use of government funds by political parties in the Special Region of Yogyakarta (DIY) during the 2019 Legislative Elections, particularly regarding campaign funds. This lack of transparency raises various issues, such as discrepancies in the reporting of fund usage, insufficient alignment in transparency, and the absence of strict sanctions from the election organizers. These conditions trigger suspicion, apathetic attitudes, and weak coordinated efforts, which potentially undermine the principles of justice in democracy. Data were collected through interviews, documentation, and analyzed descriptively based on four transparency indicators: document availability, clarity of information, process openness, and regulatory framework. The research findings indicate discrepancies and misalignment in the transparency of campaign fund reporting in the 2019 Legislative Elections, as well as minimal sanctions from the election organizers. This results in increased suspicion, apathetic attitudes, and weak coordination, which threaten the principles of justice in democracy.